(untitled) (REMUNOM, 2024)
Food and nutrition constitute basic requirements for the promotion and protection of health, enabling the full affirmation of the potential for human growth and development, with quality of life and citizenship. This study was created with the main objective of discussing the main public food and nutrition policies in Brazil and the main impacts on the population’s health. To meet the objective of this research, a bibliographical review of the literature was carried out, with a descriptive and qualitative approach. In the population, it appears that the pattern of food consumption is characterized by low intake of fruits and vegetables and excessive consumption of drinks and processed foods and fast-food snacks. Therefore, the increasingly frequent adoption of inappropriate eating habits. The present study aims to investigate in scientific literature how public policies can promote healthy eating habits, in order to encourage and teach the adoption of a balanced and nutritious diet from childhood. The choice of the topic is justified by the need to promote healthy eating habits from an early age in order to prevent diseases, improve academic performance, among other relevant factors. It is expected that the interventions will have positive effects with better awareness about eating habits.